2019
DOI: 10.3390/f10100844
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Influence of Eucalypt Plantation on Wildfire Occurrence in the Brazilian Savanna Biome

Abstract: In the last decades, eucalypt plantations are expanding across the Brazilian savanna, one of the most frequently burned ecosystems in the world. Wildfires are one of the main threats to forest plantations, causing economic and environmental loss. Modeling wildfire occurrence provides a better understanding of the processes that drive fire activity. Furthermore, the use of spatially explicit models may promote more effective management strategies and support fire prevention policies. In this work, we assessed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 72 publications
(119 reference statements)
0
5
0
Order By: Relevance
“…Studies in several parts of the world such as Brazil, Chile, and Spain have revealed that fast‐growing, densely stocked, tree plantations can support large‐scale, high‐severity wildfires (Gómez‐González, Ojeda & Fernandes, 2018; McWethy et al ., 2018, de Castro Galizia & Rodriguez, 2019). For example, in the decade between 1996 and 2005, 3–4% of Portugal's eucalypt and pine plantations burnt annually (Rego, Louro & Constantino, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in several parts of the world such as Brazil, Chile, and Spain have revealed that fast‐growing, densely stocked, tree plantations can support large‐scale, high‐severity wildfires (Gómez‐González, Ojeda & Fernandes, 2018; McWethy et al ., 2018, de Castro Galizia & Rodriguez, 2019). For example, in the decade between 1996 and 2005, 3–4% of Portugal's eucalypt and pine plantations burnt annually (Rego, Louro & Constantino, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…-High temperatures along with low relative humidity and soil moisture are conditions that increase the risk of fires, and systems with trees potentially minimize these impacts and therefore reduce fire risks, such as on crop-livestock-forest integration and livestock-forest integration (Kichel et al 2014), agroforestry system (Tscharntke et al 2011) and native forest (White & Silva 2016); -Trees, shrubs and litter may behave as fuel for wildfires, and planted forests are particularly listed as a potential land use that increases fire risk (Galizia & Rodrigues 2019); -At a local scale, incorporating trees may be hydrologically advantageous in the long term (Zimmermann et al 2006), but not immediately after implementation (Ferraz et al 2014). In fact, water gains are from improved infiltration and higher storage of water in the soil and aquifers that overcome the evapotranspiration losses (Bruijnzeel 2004); -Crop-livestock integration systems in the Cerrado region, in areas with longer dry spells (15 to 31 days) during the growing season, showed a greater resilience with little change in yield (Alvarenga et al 2021); -Intercropping systems with trees may be critical for crops during a drought event, due to the higher capacity of water absorption by trees (Souza et al 2017).…”
Section: Factorsmentioning
confidence: 99%
“…For instance, a single wildfire in 2017 destroyed more than 1,300 hectares of eucalypt plantations, causing an estimated economic loss of 5 million US$, and threatening several communities across the studied extent (Galdiole, 2017). Fire is culturally used to clear and open large areas for agriculture and extensive livestock breeding; thus, humans are responsible for most fire ignitions (Eva and Lambin, 2000;Galizia and Rodrigues, 2019;Jepson, 2005;Mistry, 2002). The region is characterized by low population density (4.8 inh km -²) with a predominance of rural settlements (IBGE, 2012).…”
Section: Study Areamentioning
confidence: 99%
“…Model outcomes suggested that fire occurrence was mainly explained by the proximity to agricultural and urban interface areas. See Galizia and Rodrigues (2019) for further details about the methods and model performance. Based on the aforementioned ignition probability grid, we generated a set of spatially-balanced 50,000 ignition points over burnable areas to saturate the landscape with wildfire (Stevens and Olsen, 2004).…”
Section: Ignition Patternmentioning
confidence: 99%